Generation of human induced pluripotent stem cell lines UKJi001-A and UKJi006-A from patients with heterozygous mutation in the PKP2 gene - Mohamed M. Bekhite; Sascha Hübner; Tom Kretzschmar; Claudia Backsch; Anja Weise; Elisabeth Klein; Juergen Bogoviku; Julian Westphal; P. Christian Schulze (Stem Cell Research)
One of the main signs we do not know enough about arrhythmogenic right ventricular dysplasia 9/cardiomyopathy (ARVCD9, OMIM #609040, autosomal dominant) is the lack of early markers and therapeutic alternatives. To better study disease pathways in vitro, we generated human induced pluripotent stem cell (hiPSC) lines from the father (UKJi006-A) and son (UKJi001-A), who both shared the same heterozygous mutation in the PKP2 gene (OMIM *602861). While the father had a clinical diagnosis of ARVC, the son lacked the ARVC phenotype. To generate hiPSC lines, non-integrating Sendai virus (SeV) vectors expressing the reprogramming factors (OCT4, SOX2, KLF4, and c-MYC) were used for reprogramming patient peripheral blood mononuclear cells (PBMCs).